Benthic communities under methane gradient in the Laptev and East Siberian seas - Konovalova, Olga; Rimskaya-Korsakova, Nadezhda; Kuznetsov, Petr; Osadchiev, Alexander; Fedyaeva, Maria; Moiseeva, Iuliia; Purgina, Darya; Kosmach, Denis; Semiletov, Igor (Frontiers in Ecology and Evolution, 2024)
IntroductionMethane seeps influence surrounding benthic communities in different ways from slight changes in benthic abundance and biomass to major altering the species composition.Materials and MethodsWe studied benthic communities of 14 methane seep flares in Laptev and East Siberian seas with comparative analysis of species composition and abiotic parameters at the nearby areas not affected by methane seeps. The species diversity was comparable at seep and non-seep sites varying from 3.9 to 39.6 taxa per 100 individuals and from 4.5 to 34.8 taxa per 100 individuals, correspondingly.ResultsThe Laptev Slope community corresponds with the Polychaeta-community, encircling the upper continental slope area of the entire Siberian Arctic. The Lower Shelf community described in this study apparently corresponds with the Ophiocten sericeum community identified in the shelf areas of the Kara, Laptev and East Siberian seas. The Upper Shelf community is mostly inhabited by the bivalves species such as Portlandia arctica, Ennucula tenuis and Astarte montagui communities. The Estuarine community, which is the poorest by diversity but has high values of abundance and biomass is directly influenced by the Lena River runoff in terms of lower salinities and higher sedimentation rates.DiscussionThroughout the study area, the differences between the Estuarine, Upper Shelf, Lower Shelf and Laptev Slope communities exceeded the differences between the seep and background non-seep areas. Several taxa demonstrated correlations with different environmental factors, including the latitude, depth, temperature, salinity, pH and methane content, not depending on the revealed benthic community. Eight taxa demonstrated correlations with the methane content measured at different sediment depths. Two siboglinids taxa demonstrated high abundances at stations with highest methane content deep in the sediment. At the Siberian shelf, our geochemical data for siboglinid habitats are the first to be published so far.